2017
DOI: 10.4317/jced.53520
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and periodontal health status among khat chewers. A case-control study

Abstract: BackgroundHabitual khat chewing is a widespread male habit in Southern Arabia and East Africa. The aim of this study was to assess the effect of Khat chewing on oral hygiene and periodontal health status among Yemeni male khat chewers.Material and MethodsThis case- control study included 310 khat chewers, aged 20-65 years, and 72 age- and gender- matched non-chewers as controls. Periodontal examination included recording of dental plaque index (PI), gingival index (GI), probing pocket depth (PPD), attachment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…One study ( 15 ) reported that khat chewers had significantly better oral hygiene status and less gingivitis compared to non-chewers whereas one study ( 14 ) found no significant differences in PI and CI among chewers and non-chewers. In contrast, majority of the included studies ( 2 , 12 , 13 , 19 , 21 ) have reported that khat chewers had reportedly overall poorer oral hygiene status reflected by their plaque scores and calculus deposits compared to the non-chewers.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…One study ( 15 ) reported that khat chewers had significantly better oral hygiene status and less gingivitis compared to non-chewers whereas one study ( 14 ) found no significant differences in PI and CI among chewers and non-chewers. In contrast, majority of the included studies ( 2 , 12 , 13 , 19 , 21 ) have reported that khat chewers had reportedly overall poorer oral hygiene status reflected by their plaque scores and calculus deposits compared to the non-chewers.…”
Section: Resultsmentioning
confidence: 94%
“…AL-Maweri and Al-Akhali ( 12 ) in their case-control study found that khat chewers had a higher overall mean plaque scores along with clinical attachment loss and gingival recession compared to non-chewers. However, it was observed that there were no significant differences in gingival index and probing pocket depth scores among the groups.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations